2020
DOI: 10.3390/cancers12102912
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Microenvironment in Neuroblastoma: New Players, New Mechanisms of Interaction and New Perspectives

Abstract: The contribution of the tumor microenvironment (TME) to cancer progression has been well recognized in recent decades. As cancer therapeutic strategies are increasingly precise and include immunotherapies, knowledge of the nature and function of the TME in a tumor becomes essential. Our understanding of the TME in neuroblastoma (NB), the second most common solid tumor in children, has significantly progressed from an initial focus on its Schwannian component to a better awareness of its complex nature, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 95 publications
(124 reference statements)
2
53
0
Order By: Relevance
“…However, the prognostic significance of IL-15 expression in NBL has not been explored. Low levels of NKTs in the TME are associated with worse outcome in this study, which is in agreement with previous reports [ 16 , 47 ] and in line with the cold tumor hypothesis [ 5 ] that lack of infiltrating NKTs in TME predicts poor outcome in NBL. However, this is the first study to further analyze NKT expression in the NBL TME according to the tumor’s MYCN status, demonstrating that fewer NKTs were associated with worse EFS and OS in MYCN-non-amplified NBL and with worse OS in MYCN-amplified NBL.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the prognostic significance of IL-15 expression in NBL has not been explored. Low levels of NKTs in the TME are associated with worse outcome in this study, which is in agreement with previous reports [ 16 , 47 ] and in line with the cold tumor hypothesis [ 5 ] that lack of infiltrating NKTs in TME predicts poor outcome in NBL. However, this is the first study to further analyze NKT expression in the NBL TME according to the tumor’s MYCN status, demonstrating that fewer NKTs were associated with worse EFS and OS in MYCN-non-amplified NBL and with worse OS in MYCN-amplified NBL.…”
Section: Discussionsupporting
confidence: 93%
“…New advances in immunotherapy have recognized the contribution of immune tumor microenvironment (TME) to NBL development and progression [ 4 , 5 ]. Most aggressive NBLs have amplification of the MYCN oncogene [ 6 ], which is associated with poor survival [ 7 , 8 ], and analysis of TARGET transcriptomic data has revealed that fewer natural killer (NK) and T cells are present in the TME of MYCN-amplified NBL [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In neuroblastoma, CAFs were first recognized as α-smooth muscle actin (α-SMA)-positive cells, which were associated with an increase in microvascular proliferation and poor clinical outcome [31,32]. CAFs are activated by soluble factors in the tumor proximity, such as TGF-β, and in turn release abundant tumorpromoting and angiogenic factors, thus contributing to the establishment of a refractory TME, tumor growth, and disease progression [33]. CAFs promote vascular proliferation through the angiogenic factors, vascular endothelial growth factor A (VEGF-A) and IL-8, and suppress NK and T cells through secretion of anti-inflammatory cytokines like TGF-β and IL-6 [34,35].…”
Section: The Suppressive Tumor Microenvironment Of Neuroblastomamentioning
confidence: 99%
“…Extracellular vesicles (EVs) are lipid bilayer vesicles released from the cells [ 170 ], which can be classified into three major groups (exosomes, microvesicles, and apoptotic bodies), based on their size [ 171 ]. Like cargo, EVs contain soluble proteins such as growth factors, cytokines, chemokines [ 172 ], lipids, metabolites, and nucleic acids, including regulatory microRNAs (miRs) [ 171 , 173 ]. Several studies reported that EVs play a crucial role in tumor–tumor [ 174 , 175 ] and tumor–immune cell communications [ 176 ] and affect tumor cells’ phenotype and metastatic potential [ 177 , 178 , 179 ].…”
Section: Strategies To Improve Cars In Neuroblastomamentioning
confidence: 99%
“…Several studies reported that EVs play a crucial role in tumor–tumor [ 174 , 175 ] and tumor–immune cell communications [ 176 ] and affect tumor cells’ phenotype and metastatic potential [ 177 , 178 , 179 ]. Neuroblastoma cells release EVs in their extracellular space [ 172 ]. Previous studies showed that neuroblastoma EVs induced the production of pro-tumorigenic cytokines and chemokines such as IL-6, IL-8, VEGF, and CCL2 by MSCs [ 180 ].…”
Section: Strategies To Improve Cars In Neuroblastomamentioning
confidence: 99%